MANAJEMEN STRATEGI DALAM MENINGKATAN KEMAKMURAN MASJID BESAR KECAMATAN BANGKALA KABUPATEN JENEPONTO (Fakultas Dakwah dan Komunikasi, 2020)
The results of this research indicate that the mosque management strategy in increasing prosperity of the Great Mosque of Bangkala, namely; 1) the management carries out planning while planning activities carried out by the caretaker are development activities, religious activities, religious activities, educational activities, while the implementation is development activities that include maintenance and maintenance of mosque facilities and infrastructure, mosque cleanliness and beauty, worship activities that include, yasinan , tahajjud prayer together, religious activities that include routine recitation, istimaiyah or meetings of preaching institutions in jeneponto district, studies, UMM activities (efforts to prosper the mosque), organizing educational activities, which include Qur'an education park (TPA), and to review again an activity carried out that is by way of deliberations with administrators conducted every day after evening prayers. The supporting and inhibiting factors of the management Bangkala Great Mosque are; 2) availability of adequate funds, communication and cooperation, the structured program of activities. While the inhibiting factor of the administrators of Bangkala Great Mosque in increasing prosperity of the mosque inactivity of the mosque's youth.